2023
DOI: 10.1186/s12889-023-15378-4
|View full text |Cite
|
Sign up to set email alerts
|

Current prevalence and geographic distribution of helminth infections in the parasitic endemic areas of rural Northeastern Thailand

Abstract: Background Helminth infection is a global health issue that not only causes acute helminthiasis but long-term infection may lead to complicated symptoms as well as severe complications. The World Health Organization cooperated with the Ministry of Public Health in many countries, particularly where high prevalence, spending a lot of resources for limiting the infection. In Thailand, the incidence of parasitic helminth infections was continuously declined in the last few decades according to sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In 2010 and 2015, the results of surveillance that included 17 community-based surveys demonstrated a high prevalence of > 20%, and the highest prevalence (45.7%) was observed in a community in the northeastern region 17 . In 2023, the prevalence of O. viverrini in Chaiyaphum Province, northeastern Thailand, was 7.15%, which was higher than that in the national surveillance conducted in 2019, which reported a prevalence of only 2.2% 18 . Despite a decline in the overall prevalence at the national level, many studies have indicated that the infection rate of O. viverrini remains high in several communities within the northeastern areas [17][18] .…”
Section: Moreover Based On Fecal Screening For O Viverrini Infection ...mentioning
confidence: 65%
See 1 more Smart Citation
“…In 2010 and 2015, the results of surveillance that included 17 community-based surveys demonstrated a high prevalence of > 20%, and the highest prevalence (45.7%) was observed in a community in the northeastern region 17 . In 2023, the prevalence of O. viverrini in Chaiyaphum Province, northeastern Thailand, was 7.15%, which was higher than that in the national surveillance conducted in 2019, which reported a prevalence of only 2.2% 18 . Despite a decline in the overall prevalence at the national level, many studies have indicated that the infection rate of O. viverrini remains high in several communities within the northeastern areas [17][18] .…”
Section: Moreover Based On Fecal Screening For O Viverrini Infection ...mentioning
confidence: 65%
“…In 2023, the prevalence of O. viverrini in Chaiyaphum Province, northeastern Thailand, was 7.15%, which was higher than that in the national surveillance conducted in 2019, which reported a prevalence of only 2.2% 18 . Despite a decline in the overall prevalence at the national level, many studies have indicated that the infection rate of O. viverrini remains high in several communities within the northeastern areas [17][18] .…”
Section: Moreover Based On Fecal Screening For O Viverrini Infection ...mentioning
confidence: 65%
“…Unfortunately, NTDs are largely neglected because of economic and social imbalances—they disproportionately affect those with lower socioeconomic status [ 162 , 163 ]. Parasitic infections are emblematic of developing countries, stemming from limited access to clean water, food contamination, and other unhygienic practices, among other reasons [ 164 , 165 , 166 ]. While the need to tackle NTDs has been increasingly recognised, new challenges such as drug-resistant phenotypes, lack of vaccine candidates, and the lack of research funds threaten the efficacy of efforts underway [ 167 , 168 ].…”
Section: Hybrid-capture Target Enrichment For Pathogensmentioning
confidence: 99%
“…[18][19][20], was performed by PCR amplification using species-specific primers (Table -2) [21,22]. PCR reactions were performed in a total volume of 25 μL as previously described by Martviset et al [23] using GoTaq® Hot Start Colorless Master Mix (Promega, WI, USA) in a thermal cycler (BIORAD T100 thermal Cycler, Singapore). The amplification steps consisted of 1 cycle of initial denaturation at 95°C for 2 min, followed by 30 cycles of 95°C for 30 s, 55-65°C for 45 s, and 72°C for 45 s, and a final extension at 72°C for 5 min.…”
Section: Pcr Amplificationmentioning
confidence: 99%